2012
DOI: 10.4236/ojts.2012.23014
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Pressure Support Ventilation in Major Lung Resection for High Risk Patients: Does It Matter?

Abstract: Background and purpose: Patients with severely impaired pulmonary function have an increased operative risk for major lung resection. The clinical benefits of pre-and perioperative, non-invasive pressure support ventilation (NIPSV) have up to now not been extensively evaluated. Patients with severely reduced pulmonary function were investigated in this prospective and randomised single centre clinical trial. Methods: Standard pulmonary evaluation was performed in all patients before major lung resection. To pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…The literature search in databases provided 11 studies (Agostini et al, 2013;Aguiló et al, 1997;Arbane et al, 2014;Barbagallo et al, 2012;Frolund and Madsen, 1986;Garutti et al, 2014;Lorut et al, 2014;Ludwig et al, 2011;Nery et al, 2012;Reeve et al, 2010;Roceto, Galhardo, Saad, and Toro, 2014). Additionally, two studies (Arbane, Tropman, Jackson, and Garrod, 2011;Danner et al, 2012) were identified from the reference list of a relevant article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search in databases provided 11 studies (Agostini et al, 2013;Aguiló et al, 1997;Arbane et al, 2014;Barbagallo et al, 2012;Frolund and Madsen, 1986;Garutti et al, 2014;Lorut et al, 2014;Ludwig et al, 2011;Nery et al, 2012;Reeve et al, 2010;Roceto, Galhardo, Saad, and Toro, 2014). Additionally, two studies (Arbane, Tropman, Jackson, and Garrod, 2011;Danner et al, 2012) were identified from the reference list of a relevant article.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies recruited a total of 1280 patients scheduled for lung surgery with a mean age between 51.9 (SD 5.5) (Aguiló et al, 1997) and 71.1 (SD 7.7) (Danner et al, 2012); approximately, 65% in the intervention group and 66% in the control group were male. Two studies included patients undergoing VATS (Arbane et al, 2014;Arbane, Tropman, Jackson, and Garrod, 2011).…”
Section: Populationmentioning
confidence: 99%
“…Although NIV offers the potential to improve lung function, unload respiratory muscles and reduce postoperative hypoxemia and atelectasis, randomized controlled trials have not shown consistent evidence that the addition of either NIV or continuous positive airway pressure (CPAP) to standard medical therapy offers no significant benefit (Lorut et al 2014 ; Nery et al 2012 ; Aguilo et al 1997 ; Barbagallo et al 2012 ; Danner et al 2012 ; Garutti et al 2014 ; Liao et al 2010 ; Perrin et al 2007 ). In a recent Cochrane review of eight trials involving a total of 486 patients, there were no significant differences between patients receiving NIV and control groups in terms of pulmonary complications (RR 1.03, 95% CI 0.72–1.47), intubation rates (RR 0.55, 95% CI 0.25–1.00), mortality (RR 0.60, 95% CI 0.24–1.53), length of ICU stay (mean difference − 0.75 days, 95% CI − 3.93–2.43) or length of hospital stay (mean difference − 0.12 days, 95% CI − 6.15–5.90) (Torres et al 2019 ).…”
Section: Postoperative Carementioning
confidence: 99%
“…Risk stratification of candidates for thoracic surgery is likely to be useful for selecting sub-sets of patients who may benefit from either prophylactic or therapeutic NIV. These might include patients with COPD or severely impaired respiratory function (Danner et al 2012 ; Garutti et al 2014 ; Perrin et al 2007 ) and obese patients (Stephan and Berard 2017 ). Further research is needed to clarify the potential usefulness of prophylactic or therapeutic NIV in such groups, and to determine the most efficacious scheduled regimens.…”
Section: Postoperative Carementioning
confidence: 99%
“…In the absence of guidelines resulting from clinical trials with good methodological quality, chest physiotherapists base their therapeutic choices on their beliefs or knowledge acquired at clinical practice. To get to know the reality of clinical practice, a survey is the indicated investigation method [14]. Therefore, the objective of this study was to know the lung expansion techniques applied by the chest physiotherapists who treat patients with drained and non-drained pleural effusion.…”
Section: Introductionmentioning
confidence: 99%